DANDELIONS AS MOTIF CREATION CONSTRUCT FOR READY TO WEAR - Sandra, Alek; Komariah, Arfiati Nurul (Runtas : Journal Of Arts And Culture, 2024)
The main source of ideas that form the basis for the creation of fashion works is the dandelion flower which has 2 kinds of flower petals. The form and use of dandelion flowers makes the writer interested in creating batik motifs with elements of dandelion images. The purpose of this research, among other things, is to create a batik motif design with the source of the dandelion flower idea. Apart from that, it is also to create ready-to-wear fashion designs. The next goal is to apply dandelion batik motifs to the Ready To Wear clothing that will be created in this work. The method used for this research uses the method of art creation from Gustami SP, namely data collection, design and embodiment. The technique used in the creation process is written batik technique. Furthermore, in making motifs, it is carried out using the deformation method as a form to obtain motif development. The batik coloring technique used in this batik is the dyeing process of the dip cap and the dab technique. The selection of colors to be used in the manufacture of women's ready-to-wear batik uses bright and dark colors from Remasol batik dyes. The works consist of 4 Ready To Wear clothes taken from Sanskrit entitled "Bhanuresmi", "Canduri", "Cakra" and "Samiya", and are equipped with accessories such as earrings, necklaces, rings, hats, headbands, sunglasses and hair bands.